Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1038/modpathol.2017.40
|View full text |Cite
|
Sign up to set email alerts
|

Small bowel carcinomas in celiac or Crohn's disease: distinctive histophenotypic, molecular and histogenetic patterns

Abstract: Non-familial small bowel carcinomas are relatively rare and have a poor prognosis. Two small bowel carcinoma subsets may arise in distinct immune-inflammatory diseases (celiac disease and Crohn's disease) and have been recently suggested to differ in prognosis, celiac disease-associated carcinoma cases showing a better outcome, possibly due to their higher DNA microsatellite instability and tumor-infiltrating T lymphocytes. In this study, we investigated the histological structure (glandular vs diffuse/poorly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(79 citation statements)
references
References 56 publications
0
78
1
Order By: Relevance
“…glandular histotype] in comparison with its loss to form diffuse or mixed cancerous growths, as already suggested in a previous investigation of a smaller series. 1 In addition to this architectural evaluation on the whole cancer tissue, we found that selective investigation of the tumour invasive front for foci of Tb and/or PDCs substantially improved separation of more from less aggressive cases. Moreover, a significant association of Tb and PDC with lymph node metastases was found.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…glandular histotype] in comparison with its loss to form diffuse or mixed cancerous growths, as already suggested in a previous investigation of a smaller series. 1 In addition to this architectural evaluation on the whole cancer tissue, we found that selective investigation of the tumour invasive front for foci of Tb and/or PDCs substantially improved separation of more from less aggressive cases. Moreover, a significant association of Tb and PDC with lymph node metastases was found.…”
Section: Discussionmentioning
confidence: 75%
“…This retrospective study included 47 patients with primary non-ampullary CrD-SBCs, mostly from the ileum [n = 44], two from the jejunum, and one from the duodenum. The patients, some of whom have been partly studied in previous series, 1,2,14 had surgical resection and complete survival data from 15 tertiary referral Italian inflammatory bowel disease centres participating in the Small Bowel Cancer Italian Consortium. Neuroendocrine neoplasms were excluded.…”
Section: Study Populationmentioning
confidence: 99%
See 3 more Smart Citations